Influenza Viral Manipulation of Sphingolipid Metabolism and Signaling to Modulate Host Defense System - Madhuvanthi Vijayan; Bumsuk Hahm (Scientifica)
Viruses attempt to create a distinctive cellular environment to favor viral replication and spread. Recent studies uncovered new functions of the sphingolipid signaling/metabolism during pathogenic virus infections. While sphingolipids such as sphingomyelin and ceramide were reported to influence the entry step of several viruses, sphingolipid-metabolizing enzymes could directly alter viral replication processes. Influenza virus was shown to increase the level of sphingosine kinase (SK) 1 to promote virus propagation. The mechanism involves regulation of intracellular signaling pathways, leading to the amplification of influenza viral RNA synthesis and nuclear export of viral ribonucleoprotein (RNP) complex. However, bovine viral diarrhea virus inhibits SK1 to enhance the efficacy of virus replication, demonstrating the presence of virus-specific strategies for modulation of the sphingolipid system. Therefore, investigating the sphingolipid metabolism and signaling in the context of virus replication could help us design innovative therapeutic approaches to improve human health.